Improved Treatment Outcomes by Using Patient Specific Drug Combinations in Mammalian Target of Rapamycin Activated Advanced Metastatic Cancers - Crook, Timothy; Patil, Darshana; Gaya, Andrew; Plowman, Nicholas; Limaye, Sewanti; Ranade, Anantbhushan; Bhatt, Amit; Page, Raymond; Akolkar, Dadasaheb (Frontiers in Pharmacology, 2021)
Activation of the mTOR signalling pathway is ubiquitous in cancers and a favourable therapeutic target. However, presently approved mTOR inhibitor monotherapies have modest benefits in labelled indications while poor outcomes have been reported for mTOR inhibitor monotherapy when administered in a label-agnostic setting based on univariate molecular indications. The present study aimed to determine whether patient-specific combination regimens with mTOR inhibitors and other anticancer agents selected on the basis of multi-analyte tumor interrogation (ETA: Encyclopedic Tumor Analysis) yields significant treatment response and survival benefits in advanced or refractory solid organ cancers. We evaluated treatment outcomes in 54 patients diagnosed with unresectable or metastatic solid organ cancers, of whom 3 were therapy naïve and 51 were pretreated where the cancer had progressed on 2 or more prior systemic lines. Within this cohort, 49 patients received mTOR inhibitor in combination with other targeted, endocrine or cytotoxic agents as guided by ETA and 5 patients received mTOR inhibitor as monotherapy or in combination with physician’s choice of anticancer agents (not guided by ETA). Patients were followed-up until death, withdrawal of consent, loss to follow-up or until April 2020, whichever is latest. In the ETA-guided combination regimen group, the Objective Response Rate (ORR) was 57.1%, the Disease Control rate (DCR) was 91.8%, median Progression Free Survival (mPFS) was 4.9 months and median Overall Survival (mOS) was 9.4 months. In the Clinician’s choice group, ORR was 0%, DCR was 20.0%, mPFS was 1 month and mOS was 5 months. Patient-specific combination regimens with mTOR inhibition and other anti-neoplastic agents, when selected on the basis of multi-analyte molecular and functional profiling of the tumor can yield improved outcomes over mTOR inhibitor monotherapy.